Electrocardiogram With Sinlammim Heartbeat On R12 And R47 Code In Pandemic Economy - Roikhan Mochamad Aziz (Nusantara Science and Technology Proceedings, 2022)
There are various aspects of human life in the medical field about the heart such as the circulatory system of the heart and heart rate machine with religiosity factor. This research aims to analyze the relationships among medical in the human body, the circular system of the heart, and the religiosity of heart. Materials and method: Data comes from various sources books, journals, the internet, primary data, and secondary data are also from the holy book. Primary data gets from an electrocardiogram (ECG) with the rate of the heart. The methodology uses descriptive analytics. The methods are similarity and reflexivity. The similarity between ECG and sinlammim graph. Results: R12 is the model of heart system and R47 is the physical structure of heart such as circle form, seventy beats per minutes, two chambers, and sinlammim movement. Human heart always praises to Allah and the graph of heart rate in ECG shows the symbols of sequence of prayers order. Heart praises to God with sentence of Exhale, Inhale, Sustain, and Cycle. Heart health needs to be taken care of during the pandemic economy.